UJI LETHAL TIME EKSTRAK ETANOL TEMU IRENG (Curcuma aeruginosa) SEBAGAI ANTELMINTIK PADA CACING GILIK (Ascaridia galli) SECARA IN VITRO - Nabil Radif Fardani (2023)
Worm infections are one of the most common diseases in the world, one of which is Ascariasis. Treatment of Ascariasis using anthelmintic drugs can cause various side effects. One alternative to minimize the side effects of administering synthetic drugs is to use nutritious plants, one of which is the rhizome of temu ireng (Curcuma aeruginosa). This research aims to determine the LT100 of various concentrations of temu ireng ethanol extract against A. galli in vitro. This research uses a true experimental type of research with a post-test control group design only. This study used ethanol extract of temu ireng with concentrations of 10%, 20%, 30%, 40%, 50%, and 75% which tested its effectiveness against the death of A. galli worms compared to pyrantel pamoate 1% as a positive control group and NaCl 0 .9% as a negative control. The results show that using the repeated ANOVA test, P<0.05 was obtained, followed by the post-hoc test. LT100 was obtained at each concentration, namely at 10% concentration for 9.96348 hours, 20% concentration for 7.49469 hours, 30% concentration for 6.87317 hours, 40% concentration for 7.18526 hours, 50% concentration for 6.54932 hours, 75% concentration for 4.53529 hours, and positive control pyrantel pamoate 1% for 4.10065 hours, with the most effective results at a concentration of 75%. This is due to the presence of tannin, saponin, monoterpene and sesquiterpene compounds in the temu ireng extract.